CRIMINAL RESPONSIBILITY OF PERPETRATORS OF THE CRIMINAL ACTS HOARDING OF SUBSIDIZED FUEL OIL (STUDY OF DECISION NUMBER 4/PID.SUS/2025/PN SGI) - Emi Fajri; Mustamam Mustamam; Cut Nurita (Jurnal Ilmiah METADATA, 2026)
Fuel hoarding is the activity of illegally hoarding or storing Fuel Oil in large quantities, usually to be resold at a higher price when there is a scarcity. This hoarding often targets subsidized fuel, which has a detrimental impact on the community and burdens the state's finances. The responsibility of the perpetrators of the crime of hoarding subsidized fuel oil in the Sigli District Court Decision Number 4/Pid.Sus/2025/PN Sgi the defendant was sentenced to imprisonment for 8 (four) months and a fine of Rp5,000,000.00 (five million rupiah), with the provision that if the fine is not paid, it will be replaced with imprisonment for 1 (one) month. The judge's consideration is because there is no justification and forgiveness, so that he is found guilty, as well as aggravating and mitigating matters. The mitigating factor for the defendant has never been punished while the aggravating factor is that the defendant's actions are detrimental to subsidized fuel consumers